Поведінка споживачів - Страшинська, Лариса Володимирівна (My University, 2010)
Посібник для самост роб. студ. «Поведінка споживачів» має допомогти студентам краще опанувати лекційний матеріал, поглибити вивчення теоретико-методичних основ курсу, привернути їхню увагу до основних положень тем. Manual for Self. slave. stud. "Consumer behavior" should help students to better master the lecture material, to deepen the study of the theoretical and methodological foundations of course, to draw their attention to the main provisions of the order.
Keywords: психологія споживачів; кінцевий споживач; споживчий попит; поведінка споживачів; культура; культура; psychology of consumers; the end user; consumer demand; consumer behavior; culture; кафедра маркетингу